Drones, state terrorism and international law. Issue 2 (4th May 2018) - Blakeley, Ruth
ABSTRACT: The conventional wisdom among US foreign policymakers is that drones enable precise strikes, and therefore limit collateral damage. In contrast, critics point out that many civilian casualties have ensued, and they variously cite poor intelligence and imprecision of the strikes as reasons for this. Critics have also raised concerns that the US and its allies are engaging in "lawfare" to legitimise violations of human rights law. As such, some have questioned whether academic engagement with the legal questions surrounding targeted killings amount to collusion with state attempts to legitimise human rights violations. This article will argue that by conceptualising the targeted killings programme as a form of state terrorism, we are better equipped to provide a critical analysis of the drones programme within the context of a long history of violence and terrorism which has underpinned the imperial and neo-imperial projects of the UK and US. The article will then argue that there are important similarities between the targeted killings programme, and previous UK and US counterinsurgency operations, including prior uses of air power, and operations involving the internment of terror suspects, and the targeting of specific individuals for interrogation and torture or disappearance. Common to these programmes is that they are forms of policing aimed at crushing rebellions, stifling disorder and constructing or maintaining particular political economies, through terror. Also common to these programmes are the attempts made either to conceal illicit actions, or in the event they are exposed, to shroud them in a veil of legitimacy. The article concludes by offering some brief reflections on why we should not abandon the quest to resolve the thorny legal questions around the targeted killings programme.